Utilizing GeoGebra-assisted model-eliciting activities (MEAs) in mathematics instruction enhances students' comprehension of concepts and improves their problem-solving abilities - Putri Ayu Febriani; Vera Mandailina; Abdillah Abdillah; Syaharuddin Syaharuddin; Saba Mehmood (JINoP (Jurnal Inovasi Pembelajaran), 2024)
A key goal of teaching math is for students to develop a deep understanding of concepts. This understanding is the foundation for all future learning in math. The purpose of this study was to improve students' conceptual understanding and problem-solving skills in GeoGebra-assisted mathematics learning with Model Eliciting Activities (MEAs). The quantitative method with a nonequivalent (pre-test and post-test) group design was used to answer the hypothesis. The instruments used were pre-test and post-test in the form of descriptions consisting of 5 questions. The participants in this study were 26 junior high school students. Data analysis used Paired Sample T-tests (t-test) to determine the level of conceptual understanding and problem-solving ability of students. The results of data analysis obtained that the application of Model Eliciting Activities (MEAs) assisted by GeoGebra is effective in increasing student’ understanding of mathematical concepts and student problem-solving skills. So, it is concluded that learning with the Eliciting Activities Model (MEAs) assisted by GeoGebra can improve students' conceptual understanding and problem-solving skills. In the future teachers are recommended to use Model Eliciting Activities (MEAs) assisted by GeoGebra in learning mathematics.